The Influence of Website Quality On Customer Loyalty Mediated by Customer Satisfaction of Shopee Career Women Customers - Adetya Purimartyas; Rohmat Dwi Jatmiko; Noor Aziz (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
The purpose of this study is to describe customer perceptions of shopee website quality, shopee customer satisfaction and shopee customer loyalty. The data analysis technique used scale and path range analysis. The results of the analysis show that the customer's perception of the quality of the shopee website can be found to be in the good category. Shopee customer satisfaction is in the very satisfied category. Shopee customer loyalty is included in the very loyal category. Website quality affects customer satisfaction, meaning that the better the quality of the shopee website, the customer satisfaction will increase. Customer satisfaction affects customer loyalty, meaning that with increasing customer satisfaction, customer loyalty will increase